Comparação de ensaios mecânicos e simulações numéricas em quadros de bicicleta de alumínio - Pereira, Arthur Yves (2018)
This work compares the results of computer simulations made in the SolidWorks Simulation program with real mechanical tests on Al 6061 bicycle frames. For this purpose, a historical retrospective of the bicycle and its current manufacturing process is presented. We introduce the finite element method, the failure evaluation criteria in simulations and the main normative mechanical tests to which bicycle frames are submitted. It also shows the process of physical tests and simulations. Regarding the results, an excellent level of precision was observed in the identification of points of effort concentration and failure. However, significant divergences in fatigue test results were found with the probable cause in the definition of the parameters of the S-N curves and divergences of the mechanical properties of the material.